The ANC's early years nation, class and place in South Africa before 1940 - Limb, Peter (Unisa Press, 2010)
At a time when African National Congress alliance politics are again prominent in South Africa, this nuanced study of the intersection of class and African national forces in the history of Africa’s oldest national liberation movement helps explain the deeper origins of this alliance. The book squarely places African agency at the centre of South African history and re-casts the story of the ANC in the words and actions of its own members and supporters at local and regional, as well as national, levels. In doing so, it shines a long overdue light on ordinary black activists, including politicised workers and women, and integrates these stories with those of more well-known leaders